Do You Know Where Your Children Are? - Ramsey, Paul (Theology today, 1979)
“We are a civilization without: lsquo;puberty rites,’ without ‘rites of passage,’ without rituals, ordeals, or vigils that the young must pass through to demonstrate that they can now be accepted as men and women among the elders. … So our youngsters have devised their own initiation ceremonies. For boys and girls, no longer being a virgin is one such rite of passage. For girls, getting pregnant is another ritual certification that they have attained, by rite, significance in their own right. This is all pitiful and very sad.”